PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER PADA PEMBELAJARAN IPS SD - Sutriani, Selfi; Rahmatina, Rahmatina; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract            The purpose of this research is to improve student learning outcomes in social learning by using the numbered head together type of cooperative model in V class at SDN 05 Sirukam Kab. Solok. The type of research used is Classroom Action Research using qualitative and quantitative approaches. The subjects of this study were teachers and V graders with 26 students consisting of 15 boys and 11 girls. The research was carried out in two cycles with research procedures consisting of planning, implementing, observing and reflecting. The results of this study are increasing student learning outcomes in sicial  learning in V class SDN 05 Sirukam kab. Solok by using numbered head together type of cooperative model. KEYWORDS : Learning outcomes, cooperative model numbered head together type